Using patient-reported outcome measures in psychiatric hospital care: an observational study describing an iterative implementation process in Denmark. (31st March 2022) - Kristensen, Solvejg; Holmskov, Jens; Pølund, Karen; Hjermitslev, Anne-Louise Lind; Bergh-Hanssen, Karin; Christensen, Irene Hjortlund; Bonde, Maria; Mainz, Jan
Abstract: Background: Patient-reported outcomes (PROs) are increasingly recognized as valuable sources of information to enhance our understanding of the quality of healthcare from the patient's perspective. Objective: This study aimed to describe the implementation process of the Danish nationwide PRO-Psychiatry project, including iterative tests of previously developed PRO measurement concept and an online data collection tool. Additional aims were to identify the 'best practice' for the routine use of PROs in hospital-based psychiatry and design information material about the project. Methods: We conducted an action-oriented observational study to explore the pilot implementation of the PRO-Psychiatry project, which was initiated in February 2018. The study was based on an iterative plan-do-learn approach. An inpatient unit and an outpatient unit from the same psychiatric department in the North Denmark Region were selected for the pilot implementation. The implementation was anchored in multidisciplinary implementation teams at unit level. These teams managed the implementation process according to four tasks defined by the department management. Results: The teams designed, tested, evaluated and adjusted the localized work practices relating to the use of PRO-Psychiatry. The comprehensibility of the predesigned PROs, the usability of the Information Technology(IT) system and the routine use of PROs during clinical consultations were repeatedly tested and adjusted until the functionality was satisfactory. Furthermore, the teams designed information material for patients (emails, posters, handouts and webpages) and clinicians (online clinical guidelines). The team members informed their colleagues about the progress of PRO-Psychiatry at staff meetings and rolled out the initiative through one-to-one teaching. Conclusions: The pilot implementation was deemed successful. PRO-Psychiatry was rolled out to other units in the region, and a national decision was made to pilot implement the initiative in the other four Danish regions.